Latent Classes of Bidirectional Face-to-Face and Cyber Intimate Partner Violence Among Lesbian, Gay, and Bisexual Emerging Adults: The Role of Minority Stressors - Ronzón-Tirado, Roman (Journal of interpersonal violence, 2022)
The rates of intimate partner violence have been found to be higher among lesbian, gay, and bisexual (LGB) individuals when compared with heterosexual populations. However, lesser is known about the impact of specific minority stressors experienced by LGB populations on their face-to-face intimate partner violence (IPV) and cyber IPV experiences. Using a three-step latent class approach, the present study investigated (i) the latent classes of self-reported types of face-to-face IPV and cyber IPV perpetration and victimization and (ii) their associations with LGB distal and proximal minority stressors (i.e., vicarious trauma, discrimination, family rejection, and LGB-identity disclosure). Participants were 288 LGB emerging adults in the age range of 18?29 years (bisexual: n = 168, gay: n = 72, and lesbian: n = 48). Findings showed the presence of four latent classes, namely, face-to-face IPV (n = 32; 37.5% gay, 18.8% lesbian, and 43.8% bisexual individuals), cyber IPV (n = 66; 33.3% gay, 12.1% lesbian, and 54.5% bisexual individuals), psychological and stalking cyber IPV (n = 89; 15.7% gay, 15.7% lesbian, and 68.5% bisexual individuals), and low IPV (n = 101; 23.8% gay, 19.8% lesbian, and 56.4% bisexual individuals). Furthermore, multinomial logistic regressions indicated that greater exposure to the minority stressors such as exposure to heterosexism, namely, discrimination and harassment, rejection from one?s family of origin, and exposure to vicarious trauma, as well as a lower degree of LGB-identity disclosure, largely predicted latent classes with greater probabilities of IPV exposure, namely, cyber IPV, face-to-face IPV classes, and psychological and stalking cyber IPV. Findings suggest the importance of addressing the role of minority stressors in IPV interventions and the creation of competent LGB-related services and training modules for clinicians.